Complete mitochondrial genome of the mandarin vole Lasiopodomys mandarinus (Rodentia: Cricetidae). (2nd January 2016) - Cong, Haiyan; Kong, Lingming; Liu, Zexin; Wu, Yi; Motokawa, Masaharu; Harada, Masashi; Li, Yuchun
Abstract: The complete sequence of the mitochondrial genome of the mandarin vole ( Lasiopodomys mandarinus ) was completed and annotated in this study. The circular genome is 16, 375 bp in length and contains the typical 37 genes that are arranged in the same order as that of the putative ancestor of vertebrate, 13 protein-coding genes, 22 tRNA genes, 2 rRNA genes and 2 non-coding regions. This study will provide genetic resource to clarify the taxonomic position of genus Lasiopodomys .